2021
DOI: 10.1016/j.jcmgh.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Provide a Stromal Niche for Liver Cancer Organoids That Confers Trophic Effects and Therapy Resistance

Abstract: We have successfully established murine and human 3dimensional co-culture models of primary liver tumorderived organoids with cancer-associated fibroblasts. This model system enables the study of the interactions between tumor cells and the stromal compartment and the response to anticancer drugs.BACKGROUND & AIMS: Cancer-associated fibroblasts (CAFs) play a key role in the cancer process, but the research progress is hampered by the paucity of preclinical models that are essential for mechanistic dissection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 60 publications
5
96
0
1
Order By: Relevance
“…Novel approaches for pancreatic cancer organoids include the co-culture with cancer-associated fibroblasts (CAFs) and using matched pancreatic ductal organoids. CAFs were shown to increase treatment resistance which shows the importance of tumor micro-environmental aspects on treatment efficacy ( 68 ). Using matched pancreatic ductal organoids and pancreatic cancer organoids the lack of therapeutic response of dual MEK-AKT inhibition observed in a clinical phase II trial ( 69 ) was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel approaches for pancreatic cancer organoids include the co-culture with cancer-associated fibroblasts (CAFs) and using matched pancreatic ductal organoids. CAFs were shown to increase treatment resistance which shows the importance of tumor micro-environmental aspects on treatment efficacy ( 68 ). Using matched pancreatic ductal organoids and pancreatic cancer organoids the lack of therapeutic response of dual MEK-AKT inhibition observed in a clinical phase II trial ( 69 ) was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, hypoxia, a common characteristic of the tumor micro-environment of solid tumors which greatly contributes to malignant behavior and chemo- and radioresistance does develop in organoids once they reach a certain size ( 52 ). The importance of the tumor micro-environment has also been shown by incorporating cancer-associated fibroblasts in pancreatic cancer organoids which led to increased resistance towards treatment ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also have suggested that one of the leading roles of CAFs is to produce niches to preserve CSC. CSCs produce CAFs through signaling pathways, and in contrast, CAFs maintain the spread and survival of CSCs by producing niches [ 92 , 93 ]. CAFs caused drug resistance in cancer by maintaining stemness in CSCs through secreting NRG1 and activating NF-κB, Wnt, and Notch3 signaling pathways [ 7 ].…”
Section: Cancer Stem Cells: Biology Origin and Their Nichementioning
confidence: 99%
“…Thus, 3D fibroblast cultures more accurately reflect cancer-associated fibroblast biology than 2D cultures. In 3D cultures, fibroblasts enhance organoid growth, invasion, and therapy resistance via both direct cell-cell contact as well as via paracrine signaling [ 47 , 67 , 68 , 69 ].…”
Section: Organoidsmentioning
confidence: 99%